The School Literacy Movement (GLS) and Student’s Interest in Reading at SDN 3 Suka Makmur - Nurul Wahidah; Isro’ullaili Isro’ullaili; Bayu Karunia Putra (Peneliti.net, 2023)
The Suka Makmur Village Integrated KKN has an additional program, namely the School Literacy Movement (GLS). This article also aims to present information related to the implementation of the elementary school literacy movement, as well as the background of students' low interest in reading. The School Literacy Movement Program (GLS) is carried out in two ways, namely daily routine activities and weekly activities. Routine class activities consist of a) silent reading, b) students read and other students listen, and c) the teacher tells stories. Weekly class literacy activities consist of special literacy learning classes in the library. The results of the KKN service show that (GLS) at SDN 3 Suka Makmur by KKN students can increase student literacy.